2005
DOI: 10.4049/jimmunol.174.1.233
|View full text |Cite
|
Sign up to set email alerts
|

The Immunomodulatory Effects of Novel β-Oxa, β-Thia, and γ-Thia Polyunsaturated Fatty Acids on Human T Lymphocyte Proliferation, Cytokine Production, and Activation of Protein Kinase C and MAPKs

Abstract: We have recently demonstrated that a novel n-3 long chain polyunsaturated fatty acid (PUFA) (β-oxa 21:3n-3) was a more potent and more selective anti-inflammatory agent than n-3 PUFA. To gain further insights into this technology, we synthesized other novel PUFA consisting of β-oxa, β-thia, and γ-thia compounds. All three types displayed anti-inflammatory activity. Each of the unsaturated β-oxa fatty acids showed similar inhibition of PHA-PMA-induced T cell proliferation with a parallel inhibition of TNF-β pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 51 publications
(47 reference statements)
1
17
0
Order By: Relevance
“…Although c9, t11-CLA enhances production of PGE 2 in DC, it is not involved in IL-12 suppression, as inhibition of PGE 2 using specific inhibitors did not restore IL-12 production in LPS-stimulated DC (C. E. Loscher, K. H. Mills, and H. M. Roche, unpublished observation). This is consistent with other studies, which have demonstrated that the inhibitory effects of PUFA are not dependent on production of PGE 2 (25,32); however, the involvement of other prostaglandins has not yet been investigated.…”
Section: Discussionsupporting
confidence: 92%
“…Although c9, t11-CLA enhances production of PGE 2 in DC, it is not involved in IL-12 suppression, as inhibition of PGE 2 using specific inhibitors did not restore IL-12 production in LPS-stimulated DC (C. E. Loscher, K. H. Mills, and H. M. Roche, unpublished observation). This is consistent with other studies, which have demonstrated that the inhibitory effects of PUFA are not dependent on production of PGE 2 (25,32); however, the involvement of other prostaglandins has not yet been investigated.…”
Section: Discussionsupporting
confidence: 92%
“…In order to increase n-3 PUFA levels in diet, linseed oil and fish oil are supplemented in milk based formulations (Ramaprasad et al 2004) and blending of α-linolenic acid (ALA 18:3) rich oils with edible vegetable oils are being attempted (Umesha and Naidu 2012). However, n-3 PUFAs are highly unsaturated, susceptible to autoxidation under aerobic conditions (Fritsche and Johnston 1988), cause an increase in oxidative stress through ROS production (Costabile et al 2005) and also ameliorate antioxidant defense system (Venkatraman and Pinnavaia 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Potter ( 1 ). Polyunsaturated fatty acids (PUFA) can modulate cytokine production, lymphocyte proliferation, and apoptosis ( 2,3 ). Saturated fatty acids (SFA) affect MHC I-mediated antigen presentation, impair immune response, and increase host susceptibility to infection speed sorter (Becton Dickenson).…”
mentioning
confidence: 99%